Vault’s floor security sensor with RFID access using microcontroller: article / Mohd Firdouz Bahtiar - Bahtiar, Mohd Firdouz (2009)
Precious items like money, jewellery and expensive antiques are usually kept in a vault or at home. Whether it is a bank or at home, security has been the number one priority to keep each and every item safe from theft. Although, most hi-tech security systems are expensive, the fact that it actually runs on simple mechanism such as sensors for input and some interface to communicate with the consumer i.e.: an LCD display, makes it probable for a low cost security system to be produced with the same hi-tech effects. A solution to these problems is embedded system that provides an application of RFID for access and a photo sensor for the guarding system that runs on low power and at a lower cost to compare to the commercialize security sensor. The design is just a module to demonstrate the basic function of the floor security system that will be observed by the PIC16f877a microcontroller by Microchip. The embedded system automation at such a low cost but demonstrates the same functionality as the commercialize security system paper describe an application of RFID for access whereby the system provides security surveillance towards a certain designated ground or floor. Users will be given the RFID smartcard for the access pass identity, the designated floor will then be armed with a source of light ( laser pointer as indicator should any message will be given to the user. The system uses a microcontroller for the simple algorithm of the signal processing. The algorithm for the RFID access and the security sensor was commercial software to control the microcontroller and interfacing circuits.